PELATIHAN ANDROID UNTUK SISWA / SISWI SMK NASIONAL MALANG - As'ad, Mohamad; Farida, Eni; Sami, Sri Esti Trisno (UNIVERSITAS PGRI MADIUN, 2020)
Abstract. Android training for students of Malang National Vocational School is one form of social service which is one of the elements of the tri darma perguruan tinggi and must be implemented by the academic community. This training was conducted at the STMIK PPKIA Pradnya Paramita (STIMATA) campus in Malang. This training was conducted after STIMATA lecturers received the same training from Google in the form of the